Distribution and Composition of Freshwater Fishes in Jempol and Serting River, Negeri Sembilan, Malaysia - Faisal Ali, Bin Anwarali Khan; Khairul Adha, Bin Abdul Rahim; Rovie-Ryan, Jeffrine J.; Dennis, Kelvin Pudu; Mohd Tajuddin, Bin Abdullah; Marilyn, Anak Jaoi @ Edward; Yuzine, Bin Esa (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2004)
Surveys on the distribution of fish fauna in Serting River and Jempol River, Negeri Sembilan were conducted from 24-30thMarch 2002. Collection was made at eight stations where river conditions varied from highly disturbed to undisturbed. A total of 41 fish species belonging to 16 families was identified. Analyses based on the number of individuals caught showed that 79.7% of total catch was represented by the Cyprinid. Present study showed that both rivers were inhabited by several introduced species such as Clarias gariepinus, Colossoma sp., Hypostomus sp. and Oreochromis sp. Species diversity, density and richness were also calculated for all the stations.